Phylogenetic study of the Schismatoglottis Nervosa Complex (Araceae: Schismatoglottideae) - A.P.J., Ting; Wong, Sin Yeng; J., Jamliah; Boyce, P.C (Singapore Bulletin Gardens, 2012)
The Schismatoglottis Nervosa Complex (Araceae: Schismatoglottideae) currently comprises 10 species: Schismatoglottis adoceta S.Y.Wong, S. elegans A.Hay, S. liniae S.Y.Wong, S. tessellata S.Y.Wong, S. ulusarikeiensis S.Y.Wong, S. matangensis S.Y.Wong, S. simonii S.Y.Wong, S. turbata S.Y.Wong, and S. nervosa Ridl., occurring in Borneo, with each endemic to a specific locality and most to a particular geology; and one species (S. brevicuspis Hook.f.) widespread in Peninsular Malaysia and Sumatera, where it is restricted to granites. Based on analysis of the matK region, a preliminary biogeographical hypothesis for the origins and subsequent taxagenesis of the Nervosa Complex is presented. This study also provides insight into possible evolution of localised mesophytic endemics in everwet, humid, and perhumid megathermal Sundaic forests. Two clades are resolved: one north of, and another south of, the Lupar Divide.